Integrasi Tindak Tutur (Lokusi, Ilokusi, Perlokusi) dalam Drama “Tak Ada Bintang di Dadanya” Karya Hamdy Salad : Suatu Kajian Pragmatik - Wanti Br Hombing; Mela E Ambarita; Verdi Chirstian Manalu; Juniati Br Togatorop; Ferdinand Simbolon (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study explores the use of language in the play Tak Ada Bint This study explores the use of language in the play Tak Ada Bintang di Dadanya (No Star in His Heart) by Hamdy Salad using a pragmatic approach. The main focus of this study is the role of language as a means of communication as seen through locution, illocution, and perlocution. The purpose of this study is to describe how these three types of speech acts interact in the relationships between characters. The method applied is literary analysis by examining 20 dialogues that are considered important. The findings show that locution forms the basis of literal meaning in conversation, illocution conveys the meaning of the spoken sentence, while perlocution can have an emotional impact on the listener. The interconnection between these three aspects creates a complex communication dynamic, which reveals conflict, social criticism, and the affirmation of moral values regarding the dedication of teachers as a form of worship without expecting anything in return. ang di Dadanya (No Star in His Heart) by Hamdy Salad using a pragmatic approach. The main focus of this study is the role of language as a means of communication as seen through locution, illocution, and perlocution. The purpose of this study is to describe how these three types of speech acts interact in the relationships between characters. The method applied is literary analysis by examining 20 dialogues that are considered important. The findings show that locution forms the basis of literal meaning in conversation, illocution conveys the meaning of the spoken sentence, while perlocution can have an emotional impact on the listener. The interconnection between these three aspects creates a complex communication dynamic, which reveals conflict, social criticism, and the affirmation of moral values regarding the dedication of teachers as a form of worship without expecting anything in return.